Multimodality Analysis: Verbal Representation in Mie Sedaap and Indomie Intant Noodles Video Advertisement - Karina May Hendra; Hamzah Hamzah (English Language and Literature, 2022)
This study aims to examine the difference in meaning in the verbal analysis of Mie Sedaap and Indomie instant noodles advertisements. This study aims to determine the difference in meaning in verbal analysis at the level of Systemic Functional Linguistics, namely ideational, interpersonal, and textual metafunctions. The data were analyzed using Halliday's (2006) theory of Systemic Functional Linguistics. The data is the words contained in the Mie Sedaap and Indomie ad videos. This research method uses descriptive qualitative research. The results showed that there were some differences in the two advertisements in using Systemic Functional Linguistics, namely the analysis of mood, attitude, modality, graduation, and theme. The five differences are dominated by Mie Sedaap advertisements.